2019
DOI: 10.35709/ory.2019.56.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term fertilization on soil microbial biomass and dehydrogenase activity in relation to crop productivity in an acid Inceptisols

Abstract: An effective approach for improving nutrient use efficiency and crop productivity simultaneously through exploitation of biological potential for efficient acquisition and utilization of nutrients by crops is very much needed in this current era. Thus, an attempt is made here to investigate the impact of long term fertilization in the soil ecology in rice-rice cropping system in post kharif - 2015 in flooded tropical rice (Oryza sativa L.) in an acidic sandy soil. The experiment was laid out in a randomized bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…This genetic and physiological variation leads to release of more root exudates and secondary plant metabolites near rhizospheric zone which accelerated microbial diversity. This result was in conformity with that of Purohit et al, 2019.…”
Section: Soil Microbial Activitysupporting
confidence: 91%
“…This genetic and physiological variation leads to release of more root exudates and secondary plant metabolites near rhizospheric zone which accelerated microbial diversity. This result was in conformity with that of Purohit et al, 2019.…”
Section: Soil Microbial Activitysupporting
confidence: 91%
“…The application of organics increased the dehydrogenase activity due to degradation of added materials which provides intra and extracellular enzymes and increase microbial activity in the soil [27,28]. The dehydrogenase activity of organic management soil was more than conventional management [29,30].Liming of acid soil enhanced the dehydrogenase activity of soil by creating a congenial environment for microbial growth [31] The finding of this experiment was also agreed with the findings of [12,32,33].…”
Section: Influence On Soil Dehydrogenase Activitysupporting
confidence: 77%
“…The dehydrogenase activity measured in this study increased from sowing to 60 DAS in summer and kharif maize and declined towards harvest. Similarly, [18] revealed that the dehydrogenase activity was maximum at the panicle initiation stage and thereafter it decreased in rice in acidic sandy soils of Bhubaneswar, India.…”
Section: Dehydrogenase Activitymentioning
confidence: 88%